Disclosure of Internal Audit Functions of Islamic Banks in Indonesia - Muhammad Nur A. Birton; Ari Ermawati; Ektinahati Ektinahati; Muhammad Muttaqin (Journal of Accounting and Investment, 2023)
Research aims: In the massive emerging development of the Islamic financial industry, the role of the internal audit function is in the spotlight as governance is the main issue of this industry’s sustainability. This study, therefore, aims to reveal the role of the internal audit function of Islamic banks in Indonesia.Design/Methodology/Approach: The study employed secondary data from annual and Good Corporate Governance (GCG) reports from Islamic banks in Indonesia to be analyzed with the qualitative content analysis by Schreier.Research findings: The researchers highlighted that the GCG and annual reports could uncover the role of internal audits in Islamic banks. The scope of an internal audit is divided into three essential activities: preparation of work program plans, implementation, monitoring, and follow-up on findings. In comparison, the authority is to communicate with the board of directors, board of commissioners, and audit committee, including the Sharia Supervisory Board (SSB), regarding sharia compliance.Theoretical contribution/Originality: Sharia compliance ensures the soundness and credibility of the Islamic ﬁnance industry. This study identified the role of the internal audit functions of Islamic banks using qualitative content analysis for the first time. Therefore, this study is unique in how the disclosure of internal audit function is presented.Research limitation/Implication: This study was limited in a deeper understanding of the findings as it was based on secondary data analysis. However, the researchers provide vital insights on control conduct of the role played by internal auditors of Islamic banks to satisfy every qualification needed as the role played by internal auditors is vital to pursue GCG principles.